In situ chamber for studying battery failure using high‐speed synchrotron radiography. (25th November 2022) - Pfaff, Jonas; Fransson, Matilda; Broche, Ludovic; Buckwell, Mark; Finegan, Donal P.; Moser, Stefan; Schopferer, Sebastian; Nau, Siegfried; Shearing, Paul R.; Rack, Alexander
Abstract : The developed test chamber, capable of high‐speed X‐ray imaging, was designed to perform robust in situ abuse tests on batteries in various configurations while providing a complete overview of the failure event with additional complementary measurement methods. Abstract : The investigation of lithium‐ion battery failures is a major challenge for personnel and equipment due to the associated hazards (thermal reaction, toxic gases and explosions). To perform such experiments safely, a battery abuse‐test chamber has been developed and installed at the microtomography beamline ID19 of the European Synchrotron Radiation Facility (ESRF). The chamber provides the capability to robustly perform in   situ abuse tests through the heat‐resistant and gas‐tight design for flexible battery geometries and configurations, including single‐cell and multi‐cell assemblies. High‐speed X‐ray imaging can be complemented by supplementary equipment, including additional probes (voltage, pressure and temperature) and thermal imaging. Together with the test chamber, a synchronization graphical user interface was developed, which allows an initial interpretation by time‐synchronous visualization of the acquired data. Enabled by this setup, new meaningful insights can be gained into the internal processes of a thermal runaway of current and future energy‐storage devices such as lithium‐ion cells.